Engineering microrobots for targeted cancer therapies from a medical perspective - Christine K. Schmidt (Nature Portfolio, 2020)
Microbot delivery devices are the latest development in attempts to overcome the systemic toxicity associated with classical chemotherapy. Here, the authors review the recent progress in the field with a focus on the clinical translation and potential of the research and give a future perspective on this topic.